2020
DOI: 10.7759/cureus.8622
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a Source of Medical and Epidemiological Information During COVID-19 Pandemic: A Cross-Sectional Study of Content Across Six Languages Around the Globe

Abstract: The current coronavirus disease 19 (COVID-19) outbreak has been declared to be a pandemic by the World Health Organization (WHO). It is evolving daily and has jeopardized life globally across social and economic fronts. One of the six key strategic objectives identified by the WHO to manage COVID-19 is to communicate critical information to all communities and prevent the spread of misinformation. We analyzed content on YouTube.com, a widely used web-based platform for medical and epidemiological information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 13 publications
7
55
2
4
Order By: Relevance
“… 5 , 10 Interestingly, previous studies noted outlandish claims and conspiracy theories like “pharmaceutical companies have a cure but won't sell it so everyone is dying” 10 and that the virus was linked with 5G development. 21 However, no such claims were observed from the videos in our study. Our results showed that inaccuracies in the videos were largely due to statements not being specific.…”
Section: Discussioncontrasting
confidence: 62%
“… 5 , 10 Interestingly, previous studies noted outlandish claims and conspiracy theories like “pharmaceutical companies have a cure but won't sell it so everyone is dying” 10 and that the virus was linked with 5G development. 21 However, no such claims were observed from the videos in our study. Our results showed that inaccuracies in the videos were largely due to statements not being specific.…”
Section: Discussioncontrasting
confidence: 62%
“…As most viewers do, the default YouTube “relevance” filter applied for the search. It has been shown that most people do not look beyond the first three pages of search results [ 5 , 19 ]. While YouTube used to post 20 videos on each page, it now presents search results in a continuous list.…”
Section: Methodsmentioning
confidence: 99%
“…A study of 21 countries found that the number of Google searches for “wash hands” increased with the lower speed of the COVID-19 spread [ 24 ]. However, systematic analyses and quality assessments revealed that considerable amounts of information on COVID-19 on the Internet often lack scientific rigor [ 25 , 26 , 27 , 28 ] and the share of videos contributed by government and health agencies was low [ 29 ]. Sources of COVID-19 information may have an impact on risk perception and self-protection behaviors.…”
Section: Introductionmentioning
confidence: 99%